Cyberbullying a modern form of bullying: let's talk about this health and social problem - Pietro Ferrara; Francesca Ianniello; Alberto Villani; Giovanni Corsello (BMC, 2018)
Abstract Cyberbullying or electronic aggression has already been designated as a serious public health threat. Cyberbullying should also be considered as a cause for new onset psychological symptoms, somatic symptoms of unclear etiology or a drop in academic performance. Pediatricians should be trained to play a major role in caring for and supporting the social and developmental well-being of children.